2020
DOI: 10.1111/pai.13220
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose‐oral immunotherapy for children with wheat‐induced anaphylaxis

Abstract: Background: Oral immunotherapy (OIT) use in patients with wheat anaphylaxis is not well studied. We assessed the efficacy of low-dose OIT for patients with wheatinduced anaphylaxis.Methods: Eligible subjects were aged 5-18 years with a history of wheat anaphylaxis and confirmed symptoms during oral food challenge (OFC) to 53 mg of wheat protein. After admission to the hospital for a 5-day buildup phase, patients in the OIT group gradually increased wheat ingestion to 53 mg/day and then ingested 53 mg daily at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…In the present study, we showed that sIgE to milk, casein, α‐lactalbumin, and β‐lactoglobulin were significantly reduced, and the sIgG and sIgG 4 to casein were significantly increased during low‐dose OIT with a target dose of 3‐mL. These findings are similar to those of previous low‐dose OITs 17,26‐28 . Interestingly, β‐lactoglobulin‐sIgG and β‐lactoglobulin‐sIgG 4 levels significantly increased only in the UM group.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we showed that sIgE to milk, casein, α‐lactalbumin, and β‐lactoglobulin were significantly reduced, and the sIgG and sIgG 4 to casein were significantly increased during low‐dose OIT with a target dose of 3‐mL. These findings are similar to those of previous low‐dose OITs 17,26‐28 . Interestingly, β‐lactoglobulin‐sIgG and β‐lactoglobulin‐sIgG 4 levels significantly increased only in the UM group.…”
Section: Discussionsupporting
confidence: 88%
“…Previous trials have enrolled patients of various ages, 45,46 including infants, toddlers, pre-schoolers, and adolescents. [47][48][49] However, complaining symptoms and taking oral medication are often difficult for young children, and conducting trials with children can be difficult. In addition, young children are more likely to acquire tolerance.…”
Section: Appropriate Age Group For Oitmentioning
confidence: 99%
“…Several recent trials have been conducted on low-dose OIT to assess its safety so that this therapy can be safely administered to patients. 47,48,[57][58][59][60] In the low-dose OIT protocol, the maximum target dose is lower than that used for the standard OIT protocol. Yanagida et al assessed low-dose OIT for patients with severe allergies to hen's egg, cow's milk, wheat, and peanut; the rates of moderate or severe symptoms for low-dose OIT were significantly lower than those of moderate or severe symptoms for full-dose OIT.…”
Section: Low-dose Oit For Patients With Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that patients with lower specific IgE to milk at diagnosis have a higher chance of being desensitized at the end of OIT. A report of low‐dose OIT to wheat in this same issue nicely builds on this interesting topic 10 . In addition to these two reports, the reader will find recent studies in PAI on the long‐term outcome of milk OIT, 11 as well as on low‐dose OIT for peanut 12 and egg 13 …”
mentioning
confidence: 88%